A structured judgement method to enhance mortality case note review: development and evaluation. Issue 12 (18th July 2013) - Hutchinson, Allen; Coster, Joanne E; Cooper, Katy L; Pearson, Michael; McIntosh, Aileen; Bath, Peter A
Abstract : Background: Case note review remains a prime means of retrospectively assessing quality of care. This study examines a new implicit judgement method, combining structured reviewer comments with quality of care scores, to assess care of people who die in hospital. Methods: Using 1566 case notes from 20 English hospitals, 40 physicians each reviewed 30–40 case notes, writing structured judgement-based comments on care provided within three phases of care, and on care overall, and scoring quality of care from 1 (unsatisfactory) to 6 (very best care). Quality of care comments on 119 people who died (7.6% of the cohort) were analysed independently by two researchers to investigate how well reviewers provided structured short judgement notes on quality of care, together with appropriate care scores. Consistency between explanatory textual data and related scores was explored, using overall care score to group cases. Results: Physician reviewers made informative, clinical judgement-based comments across all phases of care and usually provided a coherent quality of care score relating to each phase. The majority of comments (83%) were explicit judgements. About a fifth of patients were considered to have received less than satisfactory care, often experiencing a series of adverse events. Conclusions: A combination of implicit judgement, explicit explanatory comment and related quality of care scores can be used effectively to review the spectrum of care provided for people who die in hospital. The method can be used to quickly evaluate deaths so that lessons can be learned about both poor and high quality care.